Demand Elasticity Analysis of Islamic Banking Financing in Indonesia - Eka Fitriyanti (AFEBI Islamic Finance and Economic Review, 2017)
This research aims to analyze the elasticity of demand for Islamic bank's financing in Indonesia. The variables observed in this study is inflation and income per capita. This research uses time series of data for the period 2004-2015, which is a secondary data. The Data is sourced from the central bank of Indonesia and Indonesian Central Bureau of Statistics, the models used in this study is a model of multiple regression equations and Analyzed using Ordinary Least Squares (OLS). Based on the estimates, the Research found that the inflation and income per capita significantly influence elasticity of demand for Islamic bank's financing in Indonesia. The elasticity of demand for Islamic bank's financing is inelastic to changes in price. This means that the demand Islamic bank's financing in Indonesia are not sensitive to changes in price. So, Islamic banks must be-able using other factors for growth Reviews their financing.Keywords: Elasticity of Demand, Income per Capita, Inflation, Islamic bank’s financing